Interconnection of Zn content, macrosegregation, dendritic growth, nature of intermetallics and hardness in directionally solidified Mg–Zn alloys - Verissimo, Nathalia C.; Brito, Crystopher; Santos, Washington L.R.; Cheung, Noé; Spinelli, José E.; Garcia, Amauri (Journal of alloys and compounds, 2016)
Mg and Mg-based alloys are lightweight metallic materials that are extremely biocompatible and have promising mechanical properties. Mg–Zn alloys have potential applications as biomaterials in the field of hard tissue engineering for load bearing applications, and are mainly produced by casting with limited further operations such as finishing by thermo-mechanical and machining of the surface. Thus, understanding the solidification behaviour of Mg–Zn alloys becomes an essential task to be accomplished. The aim of this work is to examine the interconnection of alloy Zn content/macrosegregation/scale of the dendritic microstructure/nature of intermetallics and hardness of samples obtained by transient directional solidification of four Mg–Zn alloys. Experimental growth laws relating the primary dendrite arm spacing, λ1, of directionally solidified samples to solidification thermal parameters such as the growth rate and the cooling rate are proposed. The experimental scatters of λ1 are shown to be mainly inside the range of theoretical λ1 values predicted by the Hunt-Lu model. Also, the combined effects of macrosegregation, Zn alloying and λ1 on hardness of Mg–Zn alloys are evaluated and functional equations relating λ1 to hardness are proposed. [Display omitted] •The primary dendrite spacing of Mg–Zn alloys is correlated with solidification thermal parameters.•Zn segregation along the directionally solidified castings induced two growth regimes.•The Mg-rich matrix is formed by equiaxed grains of sixfold branched dendrites.•Functional equations relating primary dendrite arm spacing to hardness are proposed.•Hardness is shown to increase with the increase in the alloy Zn content.